Elastosonographic evaluation of patients with a sonographic finding of thickened endometrium. (March 2016) - Gultekin, I.B.; Imamoglu, G.I.; Turgal, M.; Gultekin, S.; Öcal, F.D.; Alkan, A.; Kucukozkan, T.
Abstract: Objective: To evaluate if elastosonography of the endometrium can differ between normal endometrial tissue and abnormal pathology. Study design: One hundred and six women with a sonographic finding of thickened endometrium were enrolled in this study. All patients underwent B-mode scanning and elastosonography, performed by the same operator who was blinded to the study design. After sonographic evaluation, all patients underwent endometrial tissue sampling via dilatation and curettage. Histopathological results indicated that 22 patients had endometrial hyperplasia, 20 patients had endometrial polyps, and 64 patients had normal pathology results, with or without abnormal uterine bleeding. Groups were formed according to histopathological results, and ultrasonographic findings (strain ratio, endometrial thickness) were compared. Results: Median age was 46 [interquartile range (IQR) 4] years, 37 (IQR 10) years and 36 (IQR 10) years for the endometrial hyperplasia, endometrial polyps and normal pathology groups, respectively. Median age of the endometrial hyperplasia group was significantly higher compared with the endometrial polyps and normal pathology groups ( p < 0.001). Median parity was 3 (IQR 2), 2 (IQR 1) and 3 (IQR 1) for the endometrial hyperplasia, endometrial polyps and normal pathology groups, respectively; differences between the groups were not significant ( p = 0.102). No differences were found between the groups in terms of endometrial thickness ( p > 0.05). When elastosonographic strain (B/A) ratios were compared between the groups, the endometrial hyperplasia and endometrial polyps groups had significantly lower B/A ratios (higher elasticity) than the normal pathology group ( p < 0.001). There was no significant difference in B/A ratios between the endometrial hyperplasia and endometrial polyps groups ( p > 0.05). Conclusion: The elasticity of endometrial tissue, measured non-invasively via elastosonography, was similar in women with endometrial polyps and endometrial hyperplasia, but differed significantly compared with women with normal pathology who had a sonographic finding of thickened endometrium and abnormal bleeding as the presenting complaint. According to these results, elastosonography cannot be used as a diagnostic tool to differentiate between endometrial hyperplasia and endometrial polyps. However, elastosonography can be used to differentiate between pathological endometrial changes and normal endometrium in patients presenting with a sonographic finding of thickened endometrium.